Optimization research on inductor structural parameters for post-weld electromagnetic induction heating pulsation aging treatment of large aluminum components - Fei Xue; Diqiu He; Haibo Zhou; Hua Zhou; Youqing Sun (Case Studies in Thermal Engineering)
Conventional aging methods cannot be applied to strengthen the welding joints of large aluminum components. In this regard, this paper innovatively proposes an electromagnetic induction heating pulsation aging (EIHPA) technique and further develops an optimizing strategy of the inductor structural parameters to obtain a uniform temperature field during EIHPA processes of large 2219 components. The optimization strategy combines finite element (FE) simulations, large-scale EIHPA experiments, orthogonal designs, partial least squares (PLS) regression analysis and grid search approach. A magnetothermal bi-directional coupling FE model is developed to predict the temperature fields under different structural factors. The established FE model is further validated by measuring temperatures at different positions during large-scale EIHPA experiments. Using orthogonal designs, we determined 25 groups of setups in the FE models to explore the effects of 5 most common inductor structural parameters on the temperature field. We finally obtained a group of optimized structural parameters by using PLS regression to analyze the FE modeling results, achieving a relatively uniform temperature field. The EIHPA technique and the optimization framework in this study can be potentially extended to improve welding strengths of different materials (e.g. iron, aluminum) arising from various welding techniques (e.g. friction stir welding, laser welding).